Effect Of The Utilization Of Chicken Egg Shell Waste As A Lime Mixture On Ph Parameters In Mine Acid Water - Kristanto Jiwo Saputro; Heru Suharyadi; Yusmardhany Yusuf; Hanif Khalilullah; Sindi Mutika Sari; Bagoes Nur Muhammad; Nur Reza Muhammad Yusuf (Green Publisher Indonesia, 2024)
Acid mine drainage (AMD) is a significant environmental impact of coal mining, particularly in open-pit mining systems. To neutralize AMD acidity, the commonly used method involves adding quicklime (CaO). This study aims to evaluate the effectiveness of using eggshells, which contain calcium carbonate (CaCO3), as an additive to quicklime in AMD treatment. Experiments were conducted with varying doses of ground and calcined eggshells at 150°C and 300°C. The results indicate that calcining eggshells at higher temperatures enhances their effectiveness in increasing AMD pH. Without calcination, the pH increased by 1.87%, while calcination at 150°C and 300°C resulted in pH increases of 1.87% and 8.6%, respectively. However, excessive doses of eggshells may decrease pH. Therefore, using calcined eggshells as an additive to quicklime offers a more economical and environmentally friendly solution for AMD treatment.